Perbandingan Penggunaan Buffer CTAB dan Surfaktan ABS Untuk Isolasi DNA Candida albicans - Althofur Hilman Rifki; Endah Prayekti (Biotropic : The Journal of Tropical Biology, 2025)
This study aimed to compare the effectiveness of CTAB buffer and Alkyl Benzene Sulfonate (ABS) surfactant in isolating DNA from Candida albicans. The fungi were cultured in Sabouraud Dextrose Broth (SDB) for 3 days at 37°C, and the DNA isolation process was carried out through three stages: cell lysis, precipitation, and purification. The results of DNA isolation were evaluated qualitatively using electrophoresis and quantitatively using a Nanodrop Spectrophotometer. The results showed that DNA isolation was successful using Candida albicans CTAB buffer and Alkyl Benzene Sulfonate (ABS) surfactant. This was proven by visualization of genomic DNA bands from electrophoresis results and nanodrop spectrophotometer counts. The highest DNA concentration was found when using CTAB buffer with an average concentration of 65.5 ng/µl. Meanwhile, in ABS surfactant, the highest DNA concentration was found at a concentration of 12%, amounting to 31.3 ng/µl. DNA purity when using CTAB buffer and Alkyl Benzene Sulfonate (ABS) surfactant with a concentration of 12% resulted in pure results. in CTAB buffer the average DNA purity was 1.88. At a concentration of 12% Alkyl Benzene Sulfonate (ABS) surfactant, the average DNA purity was 1.81. From the results obtained, the Alkyl Benzene Sulfonate (ABS) surfactant cannot completely replace the CTAB buffer for Candida albicans DNA isolation. Alkyl Benzene Sulfonate (ABS) surfactant can be used as an alternative to CTAB buffer to obtain good DNA purity, but the concentration cannot match that of CTAB buffer.